The art of ballpoint : experimentation, exploration, and techniques in ink - Rota, Matt (Beverly, Massachusetts : Rockport Publishers, 2016)
"The Art of Ballpoint offers a historical perspective of the pen as an art medium and how it has grown in popularity. The book explores the work, methods, and themes of over 30 leading contemporary artists who draw in many styles ranging from intensely realistic classical drawings, to modern abstractions, graphic illustration, location sketching and street art styles, A detailed section on ballpoint techniques will discuss and demonstrate line drawing and crosshatching, shading and tone, photo-realism, drawing texture and pattern, working in layers, and mixing media with ballpoint. Glide through this inspiring book and enjoy the intricate and impressive works created from an everyday tool"--
Overview and history -- Contemporary classical -- Contemporary abstraction -- Illustration and design -- Sketchbook art -- Contemporary realism.
Keywords: Pen drawing -- Technique; Ball-point pens